An Investigation of Teacher's Strategies in Teaching Listening - AMIR, JONI (2013)
This study is aimed at exploring EFL teachers' strategies in teaching listening comprehension at one junior high school in Bandung. It was conducted to get detailed information about the strategies used by teachers in teaching listening comprehension. Specifically, this study is driven by three research questions. Those are (1) how does the teacher teach listening, (2) What strategies are frequently used by the teacher in teaching listening and (3) why are the strategies used in teaching listening. This study employed a case study research design which used two data collection techniques, observation and interview. Observation was used to get main data about teachers' strategies in teaching listening comprehension. Interview was used to support the data gathered from classroom observation. All of the data were analyzed by using three major phases of analyses: data reduction, data display, and conclusion drawing and verification (Miles and Huberman: 1994). After being analyzed, the data revealed that the most used teaching phases in listening comprehension were pre, while, and post listening. Meanwhile the types of strategies used were bottom-up, top-down, and interactive. Yet, among them, the bottom-up strategy was frequently used (from five times observations the teacher used dictation three times) because bottom-up strategy (dictation) was not only easy to present but also simple to prepare. Based on the findings, the teacher theoretically did not have any experience in teaching listening comprehension strategies. He practically used strategies in teaching listening in his classroom activity unconsciously.